3-Image Bit-Level Encryption Algorithm Based on 3D Nonequilateral Arnold Transformation and Hyperchaotic System. (26th November 2020) - Huang, Huiqing; Cheng, Dongsheng
Abstract : In this paper, we propose a novel 3-image bit-level encryption algorithm based on 3D nonequilateral Arnold transformation and hyperchaotic system. Firstly, the three plain images with N × M are decomposed into 8-bit planes and then they overlap into a 3D bit matrix with size N × M × 24 . Then, the 3D bit matrix is scrambled by 3D nonequilateral Arnold transformation and the scrambled 3D bit matrix is integrated and transformed into three 2D pixel-level images. Finally, the hyperchaotic system is used to diffuse the three 2D pixel-level images; then three diffused images are rearranged to be one color image, resulting in the encrypted image. Numerical simulations and analyses of the proposed encryption scheme are given to validate the feasibility and safety of the method. The statistical analyses like histogram, correlation, and entropy confirm that the proposed method can effectively resist statistical attacks and security key analysis shows that the key space is large enough to render the brute-force attack ineffective in proposed method. The differential analysis confirms that the proposed method is effective against differential attacks and the results of the experiment confirmed that the method can resist occlusion attack.